2006
DOI: 10.1158/1078-0432.ccr-06-0815
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic-Pharmacodynamic Model for Neutropenia with Patient Subgroup Identification: Comparison across Anticancer Drugs

Abstract: Purpose: Cancer chemotherapy, although based on body surface area, often causes unpredictable myelosuppression, especially severe neutropenia. The aim of this study was to evaluate qualitatively and quantitatively the influence of patient-specific characteristics on the neutrophil concentration-time course, to identify patient subgroups, and to compare covariates on systemrelated pharmacodynamic variable between drugs. Experimental Design: Drug and neutrophil concentration, demographic, and clinical chemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 42 publications
9
81
0
Order By: Relevance
“…Th e myelosuppression model could well characterize the neutrophil-time course following both the single-agent and combination therapy for all the investigated datasets and resulted in similar systemrelated parameter estimates as previously observed for other data sets [8,28]. For 5-fl uorouracil, Slope was not signifi cantly diff erent from zero i.e.…”
Section: Resultssupporting
confidence: 66%
“…Th e myelosuppression model could well characterize the neutrophil-time course following both the single-agent and combination therapy for all the investigated datasets and resulted in similar systemrelated parameter estimates as previously observed for other data sets [8,28]. For 5-fl uorouracil, Slope was not signifi cantly diff erent from zero i.e.…”
Section: Resultssupporting
confidence: 66%
“…This approach has been widely applied to various anticancer agents [10,[37][38][39] since it is simple in nature to operate with minimum number of parameters while accounting for the time delay for onset of responses and rebound phase typically observed in myelosuppression profiles. A similar approach has been also applied to chemotherapy-related thrombocytopenia [40].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that female gender is among others a significant predictor of neutropenia and is considered a risk factor in the Guidelines for the use of Colony-Stimulating factors in Managing Neutropenia [27]. However, gender was not found as a clinically relevant covariate in PK/PD models for neutropenia although a statistical significance was shown [19,28]. For BI 2536, the gender and BSA effects were not supported by recent data obtained in a Phase II study (data not shown) and therefore dose adjustment due to gender or BSA is not warranted.…”
Section: Absolute Neutrophil Count-time Profile Vpcmentioning
confidence: 99%